Family physicians' experiences with an innovative, community-based, hybrid model of in- person and virtual care: a mixed-methods study - Jonathan Fitzsimon; Kush Patel; Cayden Peixoto; Christopher Belanger (BMC, 2023)
Abstract Background Rural, remote, and underserved communities have often struggled to provide adequate access to family physicians. To bridge this gap in Renfrew County, a large, rural region in Ontario, Canada, a community- based, hybrid care model was implemented, combining virtual care from family physicians and in-person care from community paramedics. Studies have demonstrated the clinical and cost effectiveness of this model but its acceptability to physicians has not been examined. This study investigates the experiences of participating family physicians. Methods A mixed-methods study, combining physician questionnaire response data and qualitative thematic analysis of focus group interview data. Results Data was collected from n = 17 survey respondents and n = 9 participants in two semi-structured focus groups (n = 4 and n = 5 respectively). Physicians reported high satisfaction, driven by skills development and patient gratitude, and felt empowered to reduce ED visits, care for unattached patients, and address simple medical needs. However, physicians found it difficult to provide continuous care and were sometimes unfamiliar with local healthcare resources. Conclusion This study found that a hybrid model of in-person and virtual care from family physicians and community paramedics was associated with positive physician experiences in two main areas: clinical impacts, especially avoiding unnecessary ED visits, and physician satisfaction with the service. Potential improvements for this hybrid model were identified, and include better support for patients with complex needs, and more information about local health-system services. Our findings should be of interest to policymakers and administrators seeking to improve access to care through a hybrid model of in-person and virtual care.